Studi Literatur Pendekatan Lanskap Biofilik dan Pengaruhnya terhadap Percepatan Penyembuhan untuk Implementasi di Jakarta Heart Center - Sonery, Novia; Firmansyah; Gunaedi, Rhizky Annisa Ridyna (Jurnal Lanskap Indonesia, 2025)
The biophilic design principle emphasizes how humans can live alongside nature and even within natural environments themselves and important for human’s healths as humans fundamentally should live with nature. Biophilic landscape designs have been studied and implemented in healthcare departments due to their positive impacts on mental, psychological, and physical recovery processes. This literature study aims to analyse, compare, and condense the literature on biophilic landscaping approaches to identify relevant elements suitable for potential application within Jakarta Heart Center for its Heart Medical Rehabilitation Program. The methodology used included a literature review method to identify and draw conclusions from previous studies on a specific topic. Gathered biophilic element form study findings are effectively incorporated and applied into Jakarta Heart Center through various strategies such as installing nature represented wall painting, plotting plants indoors, using natural materials for indoors and rooftop, and presenting natural sound through water feature. Drawing from proven implementation strategies adapted from several hospitals, this study focuses on Jakarta Heart Center—a standard international facility specializing in heart disease treatment—that already utilizing its rooftop spaces. The primary goal of implementing these biophilic approaches is to influence relaxation mechanisms related to heartbeat rate, respiratory rhythm, and blood pressure levels and provide a relaxation environment. The implementation strategy and design elements was modified to align with Jakarta Heart Center's three-phase recovery program, and will serve as a guide for future applications aimed at improving rehabilitation outcomes. This comprehensive analysis provides an essential framework for integrating biophilic principles into medical facilities like Jakarta Heart Center, thereby promoting holistic healing practices aligned with contemporary sustainable design standards.